2003
DOI: 10.1007/s00418-003-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

The WFS1 gene, responsible for low frequency sensorineural hearing loss and Wolfram syndrome, is expressed in a variety of inner ear cells

Abstract: Heterozygous mutations in the WFS1 gene are responsible for autosomal dominant low frequency hearing loss at the DFNA6/14 locus, while homozygous or compound heterozygous mutations underlie Wolfram syndrome. In this study we examine expression of wolframin, the WFS1-gene product, in mouse inner ear at different developmental stages using immunohistochemistry and in situ hybridization. Both techniques showed compatible results and indicated a clear expression in different cell types of the inner ear. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…WFS1 is expressed in a variety of tissues including inner ear sensory cells such as outer hair cells, spiral ganglion neurons, and cochlear lateral wall fibrocytes (35,36). The minor allele of rs62283056 (frequency 0.21 in the GWAS cohort) associates with both increased hearing loss (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WFS1 is expressed in a variety of tissues including inner ear sensory cells such as outer hair cells, spiral ganglion neurons, and cochlear lateral wall fibrocytes (35,36). The minor allele of rs62283056 (frequency 0.21 in the GWAS cohort) associates with both increased hearing loss (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Thus, the less severe impact of the regulatory variant on WFS1 function may place individuals at increased risk for hearing loss when the effect of the variant is amplified in the presence of cisplatin. Functional support was provided for the gene through data that showed that WFS1 is expressed in inner ear sensory cells 53,54 and that WFS1 expression correlates with cisplatin-induced cytotoxicity. 47,48 Initial studies by Xu et al 24 and Drögemöller et al, 37 which investigated the association of rs62283056 with CIO, were unable to replicate these findings.…”
Section: Supporting Evidence For the Role Of Slc16a5 In Ciomentioning
confidence: 99%
“…The expression of wolframin is widely distributed in different cochlear cell types, including inner and outer hair cells, a variety of supporting cells, and cells of the lateral wall, spiral ganglion, and vestibule (57). It has been localized in the mouse coclea at different developmental stages from birth to postnatal day 35 (57). Thus, it is possible that WFS1 contributes to both the development and maintenance of cells in the auditory system including the coclea.…”
Section: Deafnessmentioning
confidence: 99%
“…In the inner ear, wolframin may help maintain the proper levels of calcium ions or other charged particles that are essential for hearing (57).…”
Section: Deafnessmentioning
confidence: 99%